FACILITATION OF THE CHILD CREATIVITY THROUGH MUSICAL ACTIVITY AT PRESCHOOL - Liduma, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The theoretical substantiation of the scientific article develops from the notion of fantasy by philosopher P. Dāle, the activity theory by A. Špona, the theory of five minds for future by H. Gardner, the three creativity aspects by R. Bebre. The essence of creativity structure components, human creativity holistic development, possibilities for creativity development stimulation at the sensitive preschool period have been established. The empirical research discovered that the child through musical reproductive activity accumulates self-experience due to the teacher’s support and realizes it as a self-dependent creative activity while listening to, singing, creatively manifesting the contents by movements and colours. The creativity promotion aids at preschool are the child’s spontaneous vocal and instrumental improvisation, integrative improvisation of sonorous gestures and movements.